PENGUNGKAPAN DIRI GOFAR HILMAN SEBAGAI INFLUENCER MELALUI MEDIA INSTAGRAM - Saifulloh, Muhammad; Siregar, Maria Ulfah (Universitas Prof. Dr. Moestopo (Beragama), 2019)
The purpose of this study was to find out Gofar hilman's self-disclosure as an influencer on Instagram social media and the relationship between Gofar hilman as an influencer with self-disclosure and what were revealed by Gofar Hilman on Instagram social media and the reasons for expressing these things. Using Alfred Schutz's phenomenology theory, Jauhari Window theory, the concept of new media and Computer Mediated Communication (CMC). The paradigm used is paradigm of constructivism and phenomenology methods. Self disclosure on Instagram that has network density characteristics makes Gofar Hilman prefer Instagram social media compared to features similar to Instagram on other social media, the density on social media Instagram makes Gofar Hilman as an influencer more likely to express the feelings he feels or he wanted to expose, this was related to the theory of self-disclosure put forward by Johari Window as an embodiment of how someone relates to other people who are described as a window.